Le droit pénal et les défis de la laïcisation - Cristina Ciancio (Cahiers Jean Moulin)
In the Kingdom of Italy, numerous legislative interventions have had a considerable impact on sensitive aspects of the religious feelings of Catholics. Civil marriage, cremation as a possible alternative to burial, or public education, to give examples, have been presented by the liberal ruling class as emblematic reforms of a secular policy aimed at getting rid of outdated legacies to reintegrate into the public debate the most critical choices for civil coexistence and bring them back under state tutelage. These were issues on which the positions of Catholic conservatives and secular liberals clearly differed, and the immediate political and ideological implications of which were widely perceived. The analytical perspective chosen is to consider, among other aspects, a theme that weaves between the folds of these differences and contrasts. This is an issue where these contrasts have appeared much less obvious, and consensus and contestation have polarised beyond traditional patterns. This question has represented a challenge to the secularisation of society throughout the history of the Kingdom of Italy. The condemnation and severe punishment of those who violated burials and human remains have always been considered attacks on religion, codified since the corpus of Justinian and subject to excommunication by canon law. Before separating the throne from the altar was accomplished, the Church’s condemnation of the violation of burial as sacrilege was sufficient to render it, even on the part of the secular powers, a crime that had to be punished. In the pre-unitary states of the peninsula, the hygienist and anticlerical rationalism of the Enlightenment and the Aufklarung brought about profound changes in the care and management of dead bodies and their burial. However, Italian culture and sensibility continued to express a specific resistance to the secularisation and medicalisation of death and its rituals, often in a way that was utterly detached from anchoring in the Catholic faith. The outrage over any manipulation or violation of graves and corpses transcended traditional cultural and ideological divides. But if this transversal consensus was based on the recognition of values that were not reducible to the precepts of a particular religious denomination, any attempt to build protection of burials as exclusively secularised goods proved inadequate.